2007
DOI: 10.1098/rspb.2006.0351
|View full text |Cite
|
Sign up to set email alerts
|

From selection to complementarity: shifts in the causes of biodiversity–productivity relationships in a long-term biodiversity experiment

Abstract: In a 10-year (1996-2005) biodiversity experiment, the mechanisms underlying the increasingly positive effect of biodiversity on plant biomass production shifted from sampling to complementarity over time. The effect of diversity on plant biomass was associated primarily with the accumulation of higher total plant nitrogen pools (N g m-2) and secondarily with more efficient N use at higher diversity. The accumulation of N in living plant biomass was significantly increased by the presence of legumes, C4 grasses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

42
419
7
3

Year Published

2011
2011
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 400 publications
(471 citation statements)
references
References 23 publications
42
419
7
3
Order By: Relevance
“…Specifically, we found a negative direct relationship between functional dispersion (FDis) and AGB for all eight traits and either a negative (LDMC, LeafP, WD, and H max ) or no relationship (LA, LMA, CABA, and LeafN) with CWP. The concept of NC as a driver of EF is heuristically compelling, ecologically reasonable, and supported by simulation models, experiments, and some observational studies (e.g., Tilman 1999;Cardinale et al 2007;Fargione et al 2007;Morin et al 2011). For instance, Barrufol et al (2013) found that tree species richness was positively related to biomass accumulation during tropical forest succession.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Specifically, we found a negative direct relationship between functional dispersion (FDis) and AGB for all eight traits and either a negative (LDMC, LeafP, WD, and H max ) or no relationship (LA, LMA, CABA, and LeafN) with CWP. The concept of NC as a driver of EF is heuristically compelling, ecologically reasonable, and supported by simulation models, experiments, and some observational studies (e.g., Tilman 1999;Cardinale et al 2007;Fargione et al 2007;Morin et al 2011). For instance, Barrufol et al (2013) found that tree species richness was positively related to biomass accumulation during tropical forest succession.…”
Section: Discussionmentioning
confidence: 93%
“…These conflicting patterns may be a result of a shift in the relative importance of NC and MR among sites, or may indicate that NC and MR operate simultaneously (Grace et al 2016). Though experimental studies enable stronger inference in principle (e.g., Fargione et al 2007), the resources required to manipulate compositions and the time required to observe treatment responses makes experiments more challenging in forests (but see Potvin et al 2011).…”
Section: Electronic Supplementary Materialsmentioning
confidence: 99%
“…Two hypotheses have been advanced to explain the underlying basis of the relationship between ecosystem-level processes and diversity: the magnitude of a process can be the result of the combined activities of species present (complementarity hypothesis), or the magnitude can be the result of the presence of one or a few particularly productive species more likely to be present when diversity is high (sampling hypothesis) (Loreau and Hector, 2001;Fargione et al, 2007). Distinguishing between these competing hypotheses would determine whether all methanotrophs or only select species need to be conserved or restored in order to stimulate CH 4 consumption where it has been attenuated by change in land use.…”
Section: Discussionmentioning
confidence: 99%
“…The linkage between altered trace gas emissions and microbial community structure in soil may be more than associative-contemporary models in ecology suggest a positive relationship between species diversity and the magnitude and stability of ecosystem processes catalyzed by those species (Tilman et al, 2001;Symstad et al, 2003;Fargione et al, 2007;Ives and Carpenter, 2007). Should this relationship also hold for the soil microbial communities responsible for trace gas production and consumption, opportunities may emerge for mitigating emissions.…”
Section: Introductionmentioning
confidence: 99%
“…In terms of nutrient or water use, niche complementarity refers to the fact that plants take up resources in different places within the soil profile, during different times or in different forms, and thus jointly exploit the available resource more efficiently than in monoculture, resulting in higher ecosystem functions, for example biomass production. Over the last decade, the search to find the underlying mechanisms of complementarity has often focussed on nutrients (mainly nitrogen) (e.g., Balvanera et al, 2006, Di Falco, 2012, Fargione et al, 2007 as well as -although to a lesser extent -on light (Hautier et al, 2009, Spehn et al, 2000 and water use (Caldeira et al, 2001, De Boeck et al, 2006. Also in the Jena Experiment, nitrogen and light use (Bessler et al, 2012, Gubsch et al, 2011, Roscher et al, 2011a have been reported to contribute to the overall complementarity effect (Marquard et al, 2009).…”
Section: Species Diversity and Grassland System Stabilitymentioning
confidence: 99%